2004
DOI: 10.1038/sj.npp.1300527
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for the Involvement of the Mesolimbic κ-Opioid System in the Morphine-Induced Rewarding Effect Under an Inflammatory Pain-Like State

Abstract: Recent clinical studies have demonstrated that when morphine is used to control pain in cancer patients, psychological dependence is not a major concern. The present study was undertaken to ascertain the modulation of psychological dependence on morphine under a chronic pain-like state in rats. The prototypical m-opioid receptor agonist morphine (8 mg/kg, i.p.) induced a dose-dependent place preference. In the present study, we found that an inflammatory pain-like state following formalin injection significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
96
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 18 publications
12
96
1
Order By: Relevance
“…In contrast, k-opioid receptor agonist ICI 199,441-induced G-protein activation in the amygdala was significantly increased by CFA injection, but not sciatic nerve ligation. This phenomenon is consistent with our previous findings that inflammatory pain, but not nerve injury, causes a marked activation of endogenous kopioidergic system (Ozaki et al, 2002;Narita et al, 2005). At 1 week after the sciatic nerve ligation, thermal hyperalgesia and allodynia, but not an anxiogenic effect, were observed with nerve ligation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, k-opioid receptor agonist ICI 199,441-induced G-protein activation in the amygdala was significantly increased by CFA injection, but not sciatic nerve ligation. This phenomenon is consistent with our previous findings that inflammatory pain, but not nerve injury, causes a marked activation of endogenous kopioidergic system (Ozaki et al, 2002;Narita et al, 2005). At 1 week after the sciatic nerve ligation, thermal hyperalgesia and allodynia, but not an anxiogenic effect, were observed with nerve ligation.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, this pain-like state is associated with a reduction in m-opioid receptor function in the ventral tegmental area (Ozaki et al, 2002(Ozaki et al, , 2003. We also found that an inflammatory pain-like state could cause a sustained activation of the k-opioidergic system in the nucleus accumbens, leading to suppression of the morphine-induced rewarding effect in rats (Suzuki et al, 1999;Narita et al, 2005). Taken together, these findings suggest that a state of pain may cause physiological changes in opioid transmission at supraspinal levels.…”
Section: Discussionsupporting
confidence: 57%
“…We previously reported that morphine failed to induce rewarding effects in rats that had been injected with formalin or carrageenan into the hind paw (Suzuki et al, 1996(Suzuki et al, , 2001Narita et al, 2005a). Furthermore, it has been documented that chronic pain attenuates the development of tolerance to the antinociceptive effect of morphine in rats (Vaccarino et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Compartment A was white with a mesh floor and compartment B was black with a sand-like texture floor, but both have the same size; compartment C connected the entrances to compartments A and B, and was grey with a smooth floor. Conditioned place preference tests were performed as previously reported [18] and consisted of an 8-day schedule with four distinct phases, as follows:…”
Section: Conditioning Place Preference Cpp Paradigm (Figure 1)mentioning
confidence: 99%
“…Moreover, the functional interaction between these receptors has been demonstrated in cultivated tissue, where co-administration of CXCL12, CXCR4 ligand, blocks the hyperpolarizing current induced by MOR agonists in the PAG, suggesting that chemokine secretion could lead to opioid receptor desensitization, decreasing the opioid agonists effects [14]. Another report showed that the plantar pre-administration of formalin with the inflammatory response associated abolished the reward response to morphine in a conditioned place-preference model and decreased dopamine concentration in the Nac [18].…”
Section: Introductionmentioning
confidence: 97%